Oracle Application Server 10g : J2EE Deployment and Administration - Wessler, Michael; Mulder, Erin; Harrop, Rob; Machacek, Jan (Apress, 2004)
Oracle Application Server 10 g: J2EE Deployment and Administration focuses on the latest version of Oracle's fully J2EE-certified application server (previously called Oracle9iAS). Oracle Corporation is aggressively attacking this market with a new lost-cost version of the server, as well as a program to move BEA customers onto Oracle free of charge. Adoption interest is growing rapidly amidst favorable reports regarding performance and reliability. Deploying and configuring J2EE applications are some of the trickiest processes in J2EE development, and they unfortunately receive scant attention in general J2EE texts. This book is a focused, no-frills guide to getting J2EE applications up and running on 10 g . It covers Oracle's J2EE container, OC4J (available free of charge for development purposes), in full detail. It moves on to explain how to best configure and use the various enterprise-level features that come with the commercial editions. This is the book for anyone wanting to stay ahead in the world of Oracles application servers.